A333 THE ROLE OF IMAGING IN DETERMINING PROGNOSIS FOR PRIMARY SCLEROSING CHOLANGITIS: A SYSTEMATIC REVIEW - Segal, D (J Can Assoc Gastroenterol, 2018)
BACKGROUND: Primary Sclerosing Cholangitis (PSC) is a chronic, progressive, inflammatory bile duct disease that causes fibrosis and stricturing. Resultant complications include life–threatening infection, progressive liver disease including cirrhosis, and malignant tumors. While diagnosis utilizes imaging studies extensively, the role of imaging in determining the clinical prognosis is less clear. AIMS: The aim of this study was to systematically review existing imaging indices and features that predict PSC progression. METHODS: We performed a systematic review of imaging indices and features that predict PSC progression. PubMed, EMBASE (Ovid), MEDLINE (Ovid), and the Cochrane Library (CENTRAL) from inception to November 2015 were searched for relevant studies. Pertinent data was extracted and assessed. RESULTS: The search returned 2024 results. Of the resulting twenty-five pertinent studies selected for full text review, eight were included. The two imaging modalities studied were endoscopic retrograde cholangiopancreatography (ERCP) and magnetic resonance imaging. Two imaging indices (ERCP based and MR based) have been described and partially validated. The ERCP index was validated in a second population by comparing predicted time to liver related death or liver transplant to actual outcomes. It was then updated to be more robust. The MRCP index determined via multivariate analysis for gadolinium and non-gadolium studies was found to only be predictive of transplant free survival for the non-gadolinium studies in a proof-of-concept cohort. CONCLUSIONS: Two imaging indices, one ERCP and one MR based, have been described to predict prognosis. The ERCP index has been validated in a second cohort while the MRCP index requires external validation. FUNDING AGENCIES: None